(untitled) (Research, Society and Development, 2020)
Brazil is the world’s largest producer of sugarcane; it is the main source for the production of biofuels and sugar in Brazil. During sugarcane harvesting, whether mechanized or manual, two types of losses can occur, quantitative and qualitative, in addition, cultivars can also influence these losses. In this context, the objective of this work was to evaluate the quantitative and qualitative losses of sugarcane in commercial plots in the municipality of São Pedro do Ivaí-PR according to two harvesting methods and two cultivars. The experimental design adopted was completely randomized in a 2 x 2 factorial scheme (manual or mechanized harvest and cultivars RB 966928 and RB 855156) with 20 replicates per treatment. The quantitative losses evaluated were: stump cane, tip cane, whole and shattered billets, whole cane and total losses, and qualitative losses: ºBrix, total reducing sugars, reducing sugars, apparent sucrose content, apparent purity, moisture and fiber. The greatest quantitative loss was caused by mechanical harvest, among cultivars, total loss was observed at a higher level for cultivar RB 966928 in this harvest system. In manual harvesting, RB 855156 reached the highest values for ºBrix, and when compared to mechanical harvesting, the same effect is observed for this cultivar. In manual harvesting, the apparent sucrose content was higher than in mechanical harvesting, regardless of the evaluated cultivar.